1998
DOI: 10.1007/s002239900568
|View full text |Cite
|
Sign up to set email alerts
|

Development of Avian Tibial Dyschondroplasia: Gene Expression and Protein Synthesis

Abstract: Age-dependent gene expression and protein synthesis associated with chondrocyte differentiation were evaluated in the epiphyseal growth plates of normal and tibial dyschondroplasia (TD)-afflicted chickens. In the normal growth plate, collagen type II gene is expressed mainly by chondrocytes at the upper zone of the growth plate and by the chondrocytes in the articular cartilage. Collagen type X and osteopontin (OPN) genes are expressed in the lower zone of the growth plate and in the zone of cartilage-to-bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 28 publications
1
22
0
4
Order By: Relevance
“…Our data also agree with previous findings (Wardale & Duance, 1996), and suggest that the expression of type X collagen gene is up-regulated at the early stage of the pathogenic process of TD. Reginato et al (1998) also tested whether the accumulation of type X collagen in TD cartilage results from its increased biosynthesis, which is due largely to increased expression of the gene for this collagen; and up-regulated expression of type X collagen gene has been observed in cultured TD chondrocytes by Reginato et al But up-regulated expression of type X collagen gene does not agree with findings of other who reported that chondrocytes of the TD lesion show reduced type X collagen, no change in type X collagen or type X collagen only expressed around the TD lesion (Chen et al, 1993;Pines et al, 1998;Webster et al, 2003;Rath et al, 2005). These inconsistencies may be attributed to samples collected from varying stages of the TD lesion.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Our data also agree with previous findings (Wardale & Duance, 1996), and suggest that the expression of type X collagen gene is up-regulated at the early stage of the pathogenic process of TD. Reginato et al (1998) also tested whether the accumulation of type X collagen in TD cartilage results from its increased biosynthesis, which is due largely to increased expression of the gene for this collagen; and up-regulated expression of type X collagen gene has been observed in cultured TD chondrocytes by Reginato et al But up-regulated expression of type X collagen gene does not agree with findings of other who reported that chondrocytes of the TD lesion show reduced type X collagen, no change in type X collagen or type X collagen only expressed around the TD lesion (Chen et al, 1993;Pines et al, 1998;Webster et al, 2003;Rath et al, 2005). These inconsistencies may be attributed to samples collected from varying stages of the TD lesion.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies have reported abnormal gene expression in lesioned growth plate cartilage from late stages of TD, based on immunohistochemistry, semi-quantitative real-time reverse transcriptase Á polymerase chain reaction (PCR) and in situ hybridization (Praul et al, 2000;Shirley et al, 2003;Webster et al, 2003). Genes encoding extracellular matrix molecules such as aggrecan, type II collagen, type X collagen, osteopontin and osteonectin, growth factors and hormones such as transforming growth factor-beta, PTH-related peptide and Indian Hedgehog genes, and enzymes such as carbonic anhydrase II (CA2) and matrix metalloproteinase were among those abnormally expressed (Chen et al, 1993;Knopov et al, 1995;Twal et al, 1996;Wu et al, 1996;Rath et al, 1997;Pines et al, 1998;Ben-Bassat et al, 1999;Webster et al, 2003). However, little is known about changes in expression of other genes in the early stages of TD.…”
Section: Introductionmentioning
confidence: 99%
“…TD is characterized by avascular and non-mineralize cartilage in the tibial growth plate (Tian et al, 2013). The TD is described as abnormal differentiation of GP chondrocytes, those normally lead to cartilage vascularization, mineralization and bone formation (Pines et al, 1998;Shahzad et al, 2014a). § These authors contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%
“…Eles atingem vários estágios de proliferação, passando da fase de pré hipertrofia, para hipertrofia, e finalizam no estágio de morte celular. Esta é a fase final de diferenciação dos condrócitos no disco de crescimento e possui papel relevante no processo de ossificação endocondral (Pines et al, 1998;Gerber e Ferrara, 2000;Farquarson e Jefrreis, 2000;Praul et al, 2000).…”
Section: Desenvolvimento Do Tecido óSseounclassified
“…Pines et al (1998) relataram que referente à DT as lesões possuem elevados níveis de condrócitos na fase de pré-hipertrofia e ausência de células hipertrofiadas, sugerindo que a etapa final do processo de calcificação não aconteceu devido a não expressão ou baixa expressão dos genes responsáveis pela hipertrofia dos condrócitos.…”
Section: Definição Da Discondroplasia Tibial Em Frangos De Corteunclassified